Risk assessment and management of venous thrombo-embolism in obstetric women. (7th June 2011) - Tang, Z; Marsden, P J
Abstract : Venous thrombo-embolism (VTE) occurs in 1 in 1000 pregnancies, pulmonary embolism being the leading direct cause of maternal death in the UK. Risk assessment was introduced to the trust in 2008 to identify women at increased risk and initiate thromboprophylaxis. Updated recent RCOG guidance (Nov 2009) has suggested additional risk factors for example, smoking. The aims of the study were to evaluate whether risk assessment had been performed in women with a confirmed VTE and whether correct management was initiated as per guidelines at VTE diagnosis. Also to see whether any woman's risk status differed using recent RCOG guidance. All women who had a VTE confirmed by Doppler ultrasound or lung perfusion scan/CTPA were identified by reviewing all scans requested by the obstetric team from April 2008–January 2010. Retrospective analysis of the patients' case notes was performed. 24 patients had a confirmed VTE, a much higher incidence than expected. Only two women had documentation of risk assessment. There were six women who were at increased risk of VTE who should have received thromboprophylaxis. With the new RCOG criteria, 14 women would have been at increased risk and would received thromboprophylaxis. The lack of documentation questions whether health professionals were risk assessing. A significant number of these women's VTE may have been preventable if risk assessment had been performed, with an even higher number possibly preventable using new RCOG criteria. This stresses the importance of risk assessment and the additional risk factors that are now in the new risk assessment tool.